A century of Algerian historiography: critical reflections - SADAOUI, Mustapha (The Algerian Historical Journal, 2026)
This study exposes briefly the secular march of (contemporary) Algerian historiography from the end of the 1920s to the present time. After highlighting its most important achievements and acquisitions, she tried to point out the most significant obstacles and challenges that hinder her journey. In this regard, the study focused on shedding light on its (Algerian historiography) stubbornness in remaining hostage to the first moments of its birth. Namely, it appeared as a natural reaction to the colonial historical school but it was expected that after independence, it would expand towards broader horizons, in response to the profound transformations that the country has experienced in various fields, also in harmony with the great progress made by historical science throughout the world. However, despite all this, and after a century since its appearance, it is still a prisoner of controversies with the colonial school, unable to move from emotional reaction to academic action, hence the non-existence, or even the impossibility of a true Algerian historical school.